Effects of blood flow restriction training on aerobic capacity: a systematic review and meta-analysis - Flocco, P.; Bernabei, L. (Sport Sciences for Health, 2023)
Background and purpose Numerous research studies have shown the effects of Blood Flow Restriction (BFR) training on muscle strength and hypertrophy, but there is still no comprehensive analysis of the effects on aerobic capacity. The purpose of this study was to conduct a systematic review with meta-analysis to evaluate the qualitative and quantitative results of BFR training on aerobic capacity.